Faktor-Faktor yang Mempengaruhi Audit Delay di Indonesia - Fadhila, Noriska Sitty; Surjandari, Dwi Asih (E-Jurnal Akuntansi, 2023)
This study aims to examine and analyze the effect of operational complexity, financial condition and audit opinion on audit delay with auditor specialization as a moderating variable. Sampling used a purposive sampling technique, resulting in a sample of 71 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2020 period. The study uses a panel data regression model with E-views version 12 as a research data processing application. The results show that operational complexity has a negative effect and financial conditions have a positive effect on audit delay. Meanwhile, audit opinion has no effect on audit delay. Furthermore, auditor specialization is able to moderate operational complexity and financial conditions on audit delay. However, auditor specialization is not able to moderate audit opinion on audit delay. Keywords: Audit Delay; Operational Complexity; Financial Condition; Audit Opinion; Auditor Specialization.